Study of Failure Risk on the Utilities Unit of Oil Production PT Kilang Pertamina International RU IV Cilacap by Using Failure Mode and Effect Analysis (FMEA) Method - Sugiarto, Rachmat; Mardyanto, Mas Agus (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2025)
The Utilities Unit at Pertamina RU IV Cilacap is all materials/media/facilities needed to support refinery processing operations such as electricity, steam, cooling water, clean water, compressed air, fuel, and raw water. The Utilities Unit is one of the units that has an important role in oil production at PT Pertamina International Refinery RU IV Cilacap, so it is necessary to maintain the quality and quantity of production so that there is no sudden shutdown in the Utilities Unit. Failures that may occur can be detrimental in terms of very expensive equipment repairs and can hinder the process of existing facilities such as the cessation of water treatment. Using the Fishbone Analysis and Failure Mode and Effect Analysis (FMEA) method, this research determines the risk of failure in the petroleum processing process at the Utilities unit of PT Pertamina International RU IV Cilacap Refinery. The greatest risk of failure that arises based on the calculation of the Risk Priority Number (RPN) value will be used to determine alternative recommendations for improvements. The source of failure is obtained from 2 factors, namely from the machine and material factors. The Material factor is characterized as an aspect of product quality determined by the parameter indicators of each product, while the machinery factor can be classified as an aspect of the operating conditions of each unit. The biggest risk of failure based on the Risk Priority Number (RPN) results in the Sea Water Desalination unit with a value of 60 (low category). The suggested mitigation is by checking and monitoring chemical injections and cleaning evaporators.